2019
DOI: 10.3389/fneur.2019.01261
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Multimodality Monitoring in Pediatric Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) is a leading cause of morbidity and mortality in children. Improved methods of monitoring real-time cerebral physiology are needed to better understand when secondary brain injury develops and what treatment strategies may alleviate or prevent such injury. In this review, we discuss emerging technologies that exist to better understand intracranial pressure (ICP), cerebral blood flow, metabolism, oxygenation and electrical activity. We also discuss approaches to integrating these d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 70 publications
(64 reference statements)
0
16
0
Order By: Relevance
“…[52] This technique utilizes the Doppler shift principle to obtain the red blood cell mean flow velocity from pulses of high-frequency ultrasound waves which are aimed at basal cerebral arteries; the reflection causes a change in direction and velocity, which is used to determine the CBF. [65,66] The overall sensitivity of TCD for determining brain death is 75-88% and the overall specificity is reported to be 98%. [52] However, TCD is unable to distinguish between the symptomatic and asymptomatic measurements ranging at velocities between 120 and 199 cm s À1 .…”
Section: Cerebral Blood Flow (Cbf)mentioning
confidence: 99%
See 1 more Smart Citation
“…[52] This technique utilizes the Doppler shift principle to obtain the red blood cell mean flow velocity from pulses of high-frequency ultrasound waves which are aimed at basal cerebral arteries; the reflection causes a change in direction and velocity, which is used to determine the CBF. [65,66] The overall sensitivity of TCD for determining brain death is 75-88% and the overall specificity is reported to be 98%. [52] However, TCD is unable to distinguish between the symptomatic and asymptomatic measurements ranging at velocities between 120 and 199 cm s À1 .…”
Section: Cerebral Blood Flow (Cbf)mentioning
confidence: 99%
“…[118], and ref. [66]; NR ¼ not reported. Please refer to Table 6 for an extensive comparison of the various imaging techniques.…”
Section: Volumetric Electromagnetic Phase Shift Spectroscopy (Veps)mentioning
confidence: 99%
“…Increasing evidence also suggests that model-based indices of cerebral autoregulation (CA) and brain compliance may represent potentially modifiable biomarkers of injury severity after pediatric and adult TBI [ 5 , 6 ]. Standardized processes of assessing and reporting MMM data are not well described and despite increasing use of MMM in neurocritical care, no studies have investigated the association of MMM with functional outcome or adverse events after TBI [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dysfunction in learning and memory is a type of brain sequelae in the mechanism of TBI or secondary TBI, which is mainly induced by abnormal activity in the hippocampus. Current evidence has shown that post-TBI dysfunction in learning and memory involves significantly complicated pathologies, including neuronal death and dysfunction in the synapse, hippocampus, or brain network (4)(5)(6). So far, decades of efforts have been focused on drugs that are able to improve the dysfunction in learning and memory; however, unfortunately, an effective drug that can be used for the treatment of post-TBI dysfunction in learning and memory is not yet available (7).…”
Section: ' Introductionmentioning
confidence: 99%